Repositioning Ibn ‘Aṭiyyah in the Genealogy of ‘Ilm al-Munāsabah: An Analysis of Muqaddimah al-Muḥarrar al-Wajīz - Habib Abdillah; Muhammad Afifudin Dimyathi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
The dominance of Mashriq-centric discourse in the historiography of al-munāsabah has obscured the epistemological contributions of the Andalusian tradition of exegesis. This study aims to reposition the role of Ibn ‘Aṭiyyah (d. 541 AH) as a conceptual pioneer of this discipline, long before the systematic formulations of al-Rāzī and al-Biqā’ī. Through a genealogical–historical approach combined with close textual analysis of the Muqaddimah of al-Muḥarrar al-Wajīz. This study shows that Ibn ‘Aṭiyyah had already articulated core principles of Qur’anic coherence—tartīb al-ma‘ānī (ordering of meaning), ittiṣāl al-kalām (continuity of discourse), and the rejection of fragmented interpretation—even though he did not yet use the later formal terminology of al-munāsabah. The application of these principles is demonstrated through his careful analysis of the narrative coherence in Surah Āl ‘Imrān verses 52-54, the structural-metaphorical relationship in Surah al-Nūr verses 35-37, and the global thematic continuity between the closing of Surah al-Mā’idah and the opening of Surah al-An’ām. These findings revise the dominant Mashriq-centric narrative by highlighting an Andalusian framework grounded in linguistic, structural, and practical integration as the basis for a more coherent and context-sensitive Qur’anic hermeneutics.